COMPUTER SKILLS AMONG MEDICAL LEARNERS: A SURVEY AT KING ABDUL AZIZ UNIVERSITY, JEDDAH - Mansoor, Ibrahim (Journal of Ayub Medical College Abbottabad, 2002)
Background: We conducted a survey at King Abdul Aziz University to assess computer and Internet related activities, needs, and attitudes of our medical students towards computer assisted medical learning. Methods: A questionnaire containing 16 questions was distributed among medical students. The question form was prepared to assess the computer skills among students and their involvement in computer and Internet assisted medical and clinical learning activities. Each question was followed by a four or five points containing Likert-type multiple choice answer. Results: A total of 303 medical member of the university filled the forms. Among them majorities were medical students constituting 247 (81.5%), 10 (3.3%) were interns, 9 (3%) residents and 36 (11.9%) were senior residents. 55% of the responders were male and 45% were females. The most important points with their brief responses are: Computer skills: 6.3% Not aware; 93.7% Aware. Purpose of using computer: Personal 62.5%; Professional 15%; Academic 21.9%. Software(s) used: MS office 9.4%; MS Office and Internet 31.3%; MS Office, Internet and any medical software 37%; No software 21%. Connecting to Internet or Email: Not at all 18 %; Rarely 18%; Once a week 15%; Every alternate day 25%; Daily 12.5%; Multiple times a day 9.4%. Use of Internet for medical learning: Not at all 22%; Very rarely 22%; Some times 41%; Regularly 15%. Computers and Internet can improve studies and professional skills: No not at all 6%; Yes, to some extent 41%; Yes, too much 53%. Conclusion: The use of modern computer and Internet technology will result in more effective medical education. Expansion of computer-assisted learning requires careful strategic planning, resource sharing, staff incentives, and active promotion of multidisciplinary working and effective quality control. Keywords: Computer skills among medical students, computer assisted learning, Continuous medical education CME.